KURIKULUM KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) PADA PEMBELAJARAN KEPRODIAN PPKN DAPAT MENINGKATKAN CIVIC SKILL MAHASISWA - Rahayu, Dwi Agustina (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2022)
The achievement of qualifications produced by the educational system and the national job training system, namely human resources, is able to improve the quality and competitiveness of the Indonesian nation through the Educational Personnel Education Institute. As well as an assessment system for equality of learning outcomes. The research aims to determine the prospects and readiness of the Universitas Bhinneka PGRI in Tulungagung which is positioned as an educational institution for educational staff in the Pancasila and citizenship education study programe in improving students' civic skills. This research approach is qualitative with a descriptive method of research subjects, namely the Head of the study programe, lecturers and students. The data obtained is the result of observations, interviews and documentation carried out by researchers while conducting research in the field. The research results show that the implementation of a curriculum based on Educational Personnel Education Institutions in courses in the Pancasila and Citizenship Education study programe can improve the citizenship skills of Pancasila and Citizenship Education students.